PENGARUH HARGA, KUALITAS PRODUK DAN SALURAN DISTRIBUSI TERHADAP LOYALITAS PELANGGAN SURAT KABAR HARIAN SUARA MERDEKA (STUDI KASUS PADA PELANGGAN DI KECAMATAN SEMARANG SELATAN) - Eko Nurcahyo; Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is motivated by the level of competition in the business field in Indonesia that isgetting strict in this globalization era. One product that has been competed by the manufacturer inthis era is the daily newspapers. Suara Merdeka daily newspaper has the largest market share in thecity, where 45% of the whole production is marketed in the city of Semarang. But sales figures SuaraMerdeka daily newspapers has decreased in the period 2012 to 2014. Increasing competition and theemergence of new competitors is one of the causes of the decline in salesThis research aims is detect the influence of price, product quality, distribution channel forSuara Merdeka daily newspapers customer loyalty. This type of research is explanatory research,with data collection through questionnaires, the study of literature and interviews. The samplingtechnique used purposive sampling technique. The sample in this study amounted to 87 respondentswho are customers daily newspaper Suara Merdeka in the District of South Semarang. This studyused the analytical techniques of qualitative and quantitative analysis. Quantitative analysis using thevalidity, reliability, cross tabulation, correlation coefficient, simple and multiple regression analysis,the coefficient of determination, significance test (t test and F).The results of this research approved that price (X1), product quality (X2) and distributionchannel (X3) simultaneously can influenced customer loyalty(Y). Of the three variables were analyzedsimultaneously, variable coefficient distribution channels greatest influence on customer loyalty adaily newspaper Suara Merdeka, that is equal to 0.338, while the variable quality of the productamounted to 0.276 and the variable price of 0,040. While the coefficient of determination (R2) ofvariable pricing, quality of products and distribution channels to customer loyalty is 53.6%. Thismeans that 53.6% variable customer loyalty can be explained by three variables, while the remaining46.4% is explained by other variables.Based on the results of the study, the researchers suggested that companies pay moreattention certainty in the delivery of the newspapers every day, on time delivery of the newspapersevery day and notice information when there is a delay in delivery of the newspaper so that it canincrease customer loyalty Suara Merdeka daily newspaper.